Character Education's Impact On Student Personality: Curriculum And School Practices Review - Hanafiah Hanafiah; Kushariyadi Kushariyadi; Wakhudin Wakhudin; Bernardus Agus Rukiyanto; Iwan Usma Wardani; Anuar Ahmad (At-Ta'dib, 2024)
The development of a student's personality is a crucial aspect of their educational journey, laying the foundation for their future success and well-being. Character education has been recognized as a vital component of this process, aiming to cultivate values, attitudes, and behaviors essential for personal and social growth. This review examines the role of character education in shaping student personality, focusing on both curriculum and school practices. The study discusses theoretical frameworks underpinning character education, including the significance of values, moral development, and social-emotional learning. It explores curriculum design and implementation, highlighting challenges and opportunities in integrating character education into existing curricula. Additionally, the review investigates the role of school practices, emphasizing the involvement of teachers, parents, and the broader school community. Strategies such as character-based lesson plans, extracurricular activities, and community service projects are examined. Findings suggest that character education significantly influences student personality development, particularly in fostering values, empathy, and social responsibility. The study underscores the importance of a collaborative approach among educators, parents, and the school community for effective implementation. Implications include the need for schools to prioritize character education in their curricula and practices. The study concludes by emphasizing the potential of character education to positively impact student personality and overall well-being, advocating for continued research and development to inform best practices in this field.